UNIVERSITY PROFESSORS QUALITY OF LIFE IN THE WEST OF PARANA STATE, BRAZIL (Fiep Bulletin - online, 2015)
This study aimed to verify and evaluate the quality of life of university professors from 2 private universities in the west of Parana state, though the instrument 'SF-36' questionnaire, comparing and co-relating the 8 aspects this questionnaire intends to evaluate: motor capacity, limitation on physical aspects, pain, general health state, vitality, social aspects, limitation on emotional aspects, and mental health, for then tracing a profile of these professors' quality of life. The study was classified as field, exploratory, and descriptive, and the sample was chosen at random, following an intention criteria regarding institution, totalizing 65 people (30 men and 35 women), with ages between 25 and 62 years-old. The results show a low average-age (38,65%) among the surveyed, and a quality of life level classified as good - over 70% in every aspect. When co-related, the aspects 'vitality' and 'mental health' were the only ones which co-related directly with all the other aspects, except with the 'age'.
Keywords: Quality of life; University professors; Life style